Kompetensi Profesional bagi Seorang Guru dalam Manajemen Kelas - Sudjoko S (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2020)
For a profesional teacher should master a class-management, especially, knows about the management functions. There are as follows; planning, directing, acting, organizing and controlling. Planning consists of curriculum, educational callender, learning schedule, semester program, and lesson plan, and they are mastered by a profesional teacher. Learning directing should succeed and pass a scoring target, mastering all of materials, learning methods, strategy and learning approaches. After finishing all of learning and teaching processes, then it is to evaluate and analysis to make a good program on the other time. The objective of this research is how to improve compentence teacher in classes management by using discussing method in this research. The research method uses of the classroom action research; it concists of two cycles, and each cycle uses four steps. They are planing, acting, actuating and reflecting.